Low-cost 3D printed inertial flow microfluidic devices for cellular isolation in liquid biopsies - Sierra Agudelo, Jessica Nathalia; Subirada, Francesc; Hendriks, Melanie; Rodriguez Trujillo, Romen; Samitier, Josep (Frontiers in Lab on a Chip Technologies, 2023)
Microfluidic devices for biomedical applications manufactured by conventional lithography often lack flexibility in design integration. Limitations in aspect ratio or in the ability to integrate microfluidic elements located in different planes reduce the available design options. Regarding this, 3D printing offers several advantages over traditional fabrication techniques. However, 3D printing technologies indeed show some limitations in the resolution of the microstructures obtained in comparison with standard lithography. We have optimized a low-cost multi-system combining standard lithography and 3D printing to design inertial flow microfluidic devices with different channels dimensions for cell concentration or isolation in blood, which are adaptable to cancer tumor cell (CTC) detection in liquid biopsies. CTC separation from complete blood using microfluidic devices often faces the challenge of leukocyte contamination due to their similar size with CTC. However, with 3D printing, we can create larger channels than those produced through lithography, enabling the use of beads coated with antibodies that bind to leukocytes expressing the CD45+ receptor. This binding results in larger particles that could be separated from the CTCs in the microfluidic devices, providing a more purified CTC sample. Microfluidic spiral structures were obtained with standard lithography for a first purification step using rectangular channel of 152 µm height and 500 µm width channels. The blood samples after processing were analyzed by flow cytometry and revealed a recovery efficiency using two different CTC models of 80±4% and 95±4%. Also, the system enables 97.5±1.89% and 83.4±3.6% depletion of erythrocytes and leukocytes respectively.In addition, single or double microfluidic spiral structures to reduce leukocyte contamination using beads were directly fabricated using stereolithography 3D printing. In the single device with a channel